Interior design : theory and process. - Sully, Anthony (London : A&C Black, 2012)
- Clarification. The present situation in the design industry##- Definition of terms##- The body and measurement. The human form##- Geometry and proportion##- Visual understanding. Perception##- Expression and meaning##- Design process. The theoretical basis that allows the design process to work##- Searching for codes.
boek